Microstructure Evolution at the Solder Joint During Isothermal Aging - Zetty Akhtar, Abd Malek; Hardinnawirda, Kahar; Siti Rabiatull Aisha, Idris; M., Ishak (IEEE, 2014)
The intermetallic compound formation and growth between Sn-3.0Ag-0.5Cu solder and surface finish, mainly immersion Au-plated Cu and immersion Sn-plated Cu were investigated in this study. This study aimed to examine the effect of different immersion types of surface finish towards the intermetallic compound formation in terms of its thickness and activation energy. In this works, evolution of microstructure at the interfacial region was studied for after reflow and isothermal aging at 150 °C, up to 1000 hours. The thickness of the intermetallic was measured using ImageJ software and activation energy was calculated using measured data. The compositions of intermetallic compound were confirmed using Scanning Electron Microscopy-Energy-dispersive X-ray spectroscopy (SEM-EDX) and its microstructure were observed using optical microscope. The cross sectional microstructure of Sn-3.0Ag-0.5Cu/ImAu joint shows that Au layer disappears completely, suggesting that it was entirely dissolved into the molten solder. The same result obtained from reflowed Sn-3.0Ag-0.5Cu/immersion Sn. The thickness of IMC layer at Sn-3.0Ag-0.5Cu /ImAu interface is similar to that at at Sn-3.0Ag-0.5Cu /ImSn interface, especially for Cu6Sn5 layer. The intermetallic growths of the intermetallic structure during isothermal aging were discussed.